Effects of Tawhidic paradigm dynamism in qualitative research - Mhd. Sarif, Suhaimi (ZR Resources, 2018)
Qualitative research has been widely accepted in all disciplines for academic as well as non-academic reasons. Realism, constructionism and pragmatism paradigms have been applied widely. However, Tawhidic paradigm has not been encouraging. This study obtained feedback through personal interview from qualitative social researchers pertaining to the inclination on applying Tawhidic Paradigm. The respondents gave positive inclination on the application of Tawhidic Paradigm given the holistic, comprehensive and balanced ontology, epistemology and methodology.